Analisis Aplikasi Kantong Lumpur pada Sungai Sebagai Upaya Pengendalian Sedimentasi Waduk - Wulandari, Dyah Ari; Ulfiana, Desyta; Parmantoro, Priyo Nugroho (Department of Civil Engineering, Diponegoro University, 2020)
Reservoir sedimentation can be overcome by reducing the amount of sediment that enters the reservoir, by building check dam. The check dam has more deposited coarse sediment load than fine sediment load. Fine sediment that escapes the check dam will flow further and eventually enter the reservoir pond. Therefore it is necessary to build a building that can capture fine sediments. Construction is planned as a system of sediment trap in irrigation channels. The purpose of this study is to analyze the possibility of applying the sediment trap in the river to deposit sediments that escape the check dam. The analysis begins with the selection of the location of the sediment trap, then calculate the dimensions of the sediment trap and the amount of sediment that has settled. Based on the analysis of the selected dimensions with several combinations of gradation of sediment grains, sediment deposition that occurs ranges from 42 - 68%. So it can be concluded making the sediment trap in the river can be done. However, for the application of these sediment traps further research is needed regarding the dimensions of sediment traps that are most optimal for sediment deposition.